1) 3x^2-12=0
2) 2x^2+6x=0
3) 1,8x^2=0
4) x^2+9=0
5) 7x^2-14=0
6) x^2-3x=0
7) (x-2)^2=3x-8
8 (x-1)^2=29-5x
9) (x+3)^2=-(x-1)^2
10) 5(x=2)^2=-6x-44
11) (-x-1)(x-4)=x(4x-11)
12) 5(x-2)=(3x+2)(x-2)

1

Ответы и объяснения

  • kiskam
  • светило науки
2013-05-28T19:55:42+04:00

1)  3x^2-12=0

  3x^2=12

x^2=4

x=+-2

 

2)  2x^2+6x=0

  2x(x+3)=0

x=0 x=-3

 

3)  1,8x^2=0

x=0

 

4)  x^2+9=0

x^2=-9

net resheniy

 

5)  7x^2-14=0

x^2-2=0

x^2=2

x=+- √2

 

6)  x^2-3x=0

x(x-3)=0

x=0 x=3

 

7)  (x-2)^2=3x-8

x^2-4x+4-3x+8=0

x^2-7x+12=0

(x-4)(x-3)=0

x=4 x=3

 

8)  (x-1)^2=29-5x

x^2-2x+1-29+5x=0

x^2+3x-28=0

(x+7)(x-4)=0

x=-7 x=4

 

9)  (x+3)^2=-(x-1)^2

x^2+6x+9=x^2-2x+1

8x=-8

x=-1

 

10) 5(x-2)^2=-6x-44

5(x^2-4x+4)+6x+44=0

5x^2-14x+64=0

D=14^2-64*4*5<0

net resheniy

 

11) (-x-1)(x-4)=x(4x-11)

-x^2+4x-x+4=4x^2-11x

5x^2-14x-4=0

D=14^2+4*5*4=276

√D=√276

x1=(14-√276)/10

x2=(14+√276)/10

 

12) 5(x-2)=(3x+2)(x-2)

5=3x+2

3x=3

x=1